The Influence of Reputation and Web Quality on Lazada Customer Trust in Pendopo District, Empat Lawang Regency, South Sumatra - Yeti Pristidayanti; Ade Tiara Yulinda (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the influence of reputation and web quality on customer trust in Lazada in Pendopo District, Empat Lawang Regency, South Sumatra. This research is a type of quantitative research. Data collection techniques are interviews, observation, literature study and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the results of research on the relationship between Web quality and reputation with customer trust in Lazada in Pendopo District, the following conclusions can be drawn: There is a positive and significant effect of Reputation (X1) on customer trust (Y) Lazada in Pendopo District, meaning that the higher the reputation, the more increase consumer confidence. There is an influence of Web quality (X2) on Lazada's customer trust (Y) in Pendopo District. meaning that the higher the relationship marketing, the more it increases consumer confidence. There is an influence of reputation and web quality which together influence the trust of Lazada customers in the Pendopo District with a Fsig value of 0.003 <0.05.